Topical Drug Delivery to the Posterior Segment of the Eye - Marina Löscher; Chiara Seiz; José Hurst; Sven Schnichels (MDPI AG, 2022)
Topical drug delivery to the posterior segment of the eye is a very complex challenge. However, topical delivery is highly desired, to achieve an easy-to-use treatment option for retinal diseases. In this review, we focus on the drug characteristics that are relevant to succeed in this challenge. An overview on the ocular barriers that need to be overcome and some relevant animal models to study ocular pharmacokinetics are given. Furthermore, a summary of substances that were able to reach the posterior segment after eye drop application is provided, as well as an outline of investigated delivery systems to improve ocular drug delivery. Some promising results of substances delivered to the retina suggest that topical treatment of retinal diseases might be possible in the future, which warrants further research.